Helping older pedestrians navigate in the city: comparisons of visual, auditory and haptic guidance instructions in a virtual environment. Issue 2 (1st February 2019) - Montuwy, Angélique; Dommes, Aurélie; Cahour, Béatrice
ABSTRACT: Preserving older pedestrians' navigation skills in urban environments is a challenge for maintaining their quality of life. However, existing aids do not take into account older people's perceptual and cognitive declines nor their user experience, and they call upon sensory modalities that are already used during walking. The present study was aimed at comparing different guidance instructions using visual, auditory, and haptic feedback in order to identify the most efficient and best accepted one(s). Sixteen middle-age (non-retired) adults, 21 younger-old (young-retired) adults, and 21 older-old (old-retired) adults performed a navigation task in a virtual environment. The task was performed with visual feedback (directional arrows superimposed on the visual scenes), auditory feedback (sounds in the left/right ear), haptic feedback (vibrotactile information delivered by a wristband), combinations of different types of sensory feedback, or a paper map. The results showed that older people benefited from the sensory guidance instructions, as compared to the paper map. Visual and auditory feedbacks were associated with better performance and user experience than haptic feedback or the paper map, and the benefits were the greatest among the older-old participants, even though the paper-map familiarity was appreciated. Several recommendations for designing pedestrian navigation aids are proposed.